Low-dose vs. standard-dose intravenous alteplase for acute ischemic stroke with unknown time of onset - Wang, Zekun; Ji, Kangxiang; Fang, Qi (Frontiers in Neurology, 2023)
Background: Standard-dose intravenous alteplase for acute ischemic stroke (AIS) in the unknown or extended time window of up to 9 hours from symptom onset is effective and safe for certain patients selected by multimodal neuroimaging. However, the therapeutic effect of low-dose alteplase beyond 4.5 hours of stroke onset remains uncertain. Methods: Consecutive AIS patients who received intravenous alteplase within 4.5 and 9 hours after symptom onset or with unknown time of onset guided by computed tomography (CT) perfusion between June 2019 and June 2022 were identified from our prospectively maintained database. The primary outcome was excellent functional recovery (modified Rankin scale [mRS] score of 0-1 at 90 days). Secondary outcomes included functional independence (mRS score of 0-2 at 90 days), early major neurologic improvement (ENI), early neurologic deterioration (END), symptomatic ICH (sICH), any intracranial hemorrhage (ICH), and 90-day mortality. Propensity score matching (PSM) and multivariable logistic regression models were used to adjust for confounding factors and compare the clinical outcomes between the low- and standard-dose groups. Results: Overall, 206 patients were included: 63 in the standard-dose group and 143 in the low-dose group. No statistically significant differences were detected between the two groups in excellent functional recovery (38.1% vs. 32.2%, adjusted odds ratio [aOR] 1.22, 95% confidence interval [CI] 0.62-2.39). Patients receiving low-dose alteplase had similar rates of functional independence, ENI, END, sICH and 90-day mortality, but a potentially lower incidence of any ICH (10.5% vs. 19.4%, aOR 2.18, 95% CI 0.84-5.65) compared to those receiving standard-dose alteplase. In the subgroup analysis, patients aged 70 years or older were more likely to achieve excellent functional recovery when receiving standard-dose than low-dose alteplase. Conclusion: Compared with standard-dose alteplase, low-dose alteplase for AIS patients with favorable perfusion-imaging profiles in the extended or unknown time window of up to 9 hours from stroke onset may exhibit similar efficacy, especially in patients younger than 70 years, and potentially reduce the risk of hemorrhagic complications. This finding suggests that low-dose alteplase may be safe and effective for AIS patients presented beyond 4.5-hour time window under the guidance of CT perfusion.